Changes in school leadership practices under an accountability system: The case of Chile - Rojas , Jorge; Carrasco, Diego (Education Policy Analysis Archives, 2021)
Accountability systems have been educational policies oriented towards school improvement. In this context, the present study examines the changes in two school leadership practices with the introduction of the accountability policy in Chile. Taking into account the responses of the fourth-grade math teachers, two scales were divised to evaluate the academic monitoring and teacher support practices implemented by school leaders between 2009 and 2012. From a multilevel analysis, changes in leadership practices were evaluated considering the context of academic performance and social vulnerability of the schools. The results show a significant change in academic monitoring under the accountability policy, but not the teaching support provided by the administrators. The implications of these results indicate that academic monitoring is normalized in schools, especially in those that were not conducting monitoring, although without affecting professional teacher support, leaving doubts about the pedagogical support and the sustainability of the accountability policy.